Genetic diversity in a commercial black soldier fly, Hermetia illucens (Diptera: Stratiomydiae), population - Badenhorst, Rozane (Stellenbosch : Stellenbosch University, 2017)
Thesis (MSc)--Stellenbosch University, 2017.